Coated magnesia particles, filler for heat dissipation material, resin composition, and method for producing coated magnesia particles

Coated magnesia particles with a specific coating thickness and sphericity address the challenge of achieving both thermal conductivity and moisture resistance, improving their performance in heat dissipation materials.

JP7608241B2Active Publication Date: 2025-01-06DENKA CO LTD
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
JP2021060018
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2021-03-31
Publication Date
2025-01-06
Estimated Expiration
2041-03-31

AI Technical Summary

Technical Problem

Existing magnesia fillers face challenges in achieving both high thermal conductivity and moisture resistance, particularly in high temperature and high humidity environments, limiting their application in heat dissipation materials.

Method used

Coated magnesia particles with a specific thickness of the coating layer and average sphericity, produced by injecting magnesia and inorganic oxide particles into a high-temperature field, ensuring both high thermal conductivity and moisture resistance.

Benefits of technology

The coated magnesia particles exhibit excellent thermal conductivity and moisture resistance, enhancing their reliability and dispersibility in resin compositions.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007608241000002
    Figure 0007608241000002
  • Figure 0007608241000001
    Figure 0007608241000001
Patent Text Reader

Abstract

To provide coated magnesia particles having both high thermal conductivity and moisture resistance.SOLUTION: One aspect of the present invention is coated magnesia particles comprising magnesia particles and a coating layer covering a surface of the magnesia particles, wherein the coating layer contains an inorganic oxide other than magnesia, a thickness of the coating layer is 0.08 to 7 μm, and an average sphericity of the coated magnesia particles is 0.90 or more.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to coated magnesia particles, a filler for a heat dissipating material, a resin composition, and a method for producing the coated magnesia particles. [Background technology]

[0002] In recent years, with the increase in communication traffic under 5G high-speed communication, the amount of heat generated by communication devices is also increasing, and there is a demand for more powerful heat dissipation components. Alumina fillers are widely used for heat dissipation components, but magnesia fillers have extremely high thermal conductivity and are therefore useful as fillers for heat dissipation materials.

[0003] However, magnesia changes to water magnesia in a high-temperature and high-humidity environment, and the thermal conductivity decreases accordingly, so the use of magnesia fillers is limited to limited environments. Therefore, various studies have been conducted to improve the moisture resistance of magnesia. For example, Patent Document 1 discloses an epoxy resin molding material that uses magnesia whose surface is coated with silica as a filler in order to improve the moisture resistance of magnesia. [Prior art documents] [Patent documents]

[0004] [Patent Document 1] Japanese Patent Application Publication No. 61-283648 Summary of the Invention [Problem to be solved by the invention]

[0005] However, when using magnesia particles whose surfaces are coated with silica or the like (coated magnesia particles), it is not necessarily easy to achieve both high thermal conductivity and moisture resistance. Therefore, one aspect of the present invention aims to provide coated magnesia particles that can achieve both high thermal conductivity and moisture resistance. [Means for solving the problem]

[0006] The present inventors have found that, in coated magnesia particles in which the surface of magnesia particles is coated with an inorganic oxide, high thermal conductivity and moisture resistance can be achieved by setting the thickness of the coating layer and the average sphericity of the coated magnesia particles within a specific range. That is, when at least one of the thickness of the coating layer and the average sphericity of the coated magnesia particles is outside the specific range, at least one of the thermal conductivity and moisture resistance is excessively deteriorated, whereas when the thickness of the coating layer and the average sphericity of the coated magnesia particles are within the specific range, such deterioration can be suppressed (high thermal conductivity and moisture resistance can be achieved at the same time). The present inventors have also found that the coated magnesia particles as described above can be obtained by a specific manufacturing method.

[0007] One aspect of the present invention is a coated magnesia particle comprising a magnesia particle and a coating layer coating the surface of the magnesia particle, the coating layer containing an inorganic oxide other than magnesia, the thickness of the coating layer being 0.08 to 7 μm, and the average sphericity of the coated magnesia particle being 0.90 or more. The average particle diameter of the coated magnesia particle may be 30 to 150 μm. The inorganic oxide may be at least one selected from the group consisting of silica and alumina.

[0008] Another aspect of the present invention is a filler for a heat dissipating material containing the above-mentioned coated magnesia particles.

[0009] Another aspect of the present invention is a resin composition containing the above-mentioned coated magnesia particles and a resin.

[0010] Another aspect of the present invention is a method for producing coated magnesia particles, comprising a step of injecting a raw material containing magnesia particles and particles of an inorganic oxide other than magnesia into a high-temperature field heated to a temperature equal to or higher than the melting point of the inorganic oxide particles to coat the surfaces of the magnesia particles and form a coating layer containing an inorganic oxide, the content of the magnesia particles in the raw material being 70 to 95 parts by mass per 100 parts by mass of the total of the magnesia particles and the inorganic oxide particles. The inorganic oxide may be at least one selected from the group consisting of silica and alumina. Effect of the Invention

[0011] According to one aspect of the present invention, it is possible to provide a coated magnesia which has excellent thermal conductivity, high moisture resistance reliability, and good dispersibility in resin. [Brief description of the drawings]

[0012] [Figure 1] FIG. 2 is a schematic cross-sectional view showing one embodiment of coated magnesia particles. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0013] In this specification, a numerical range indicated using "~" indicates a range including the numerical values ​​described before and after "~" as the minimum and maximum values, respectively. In the numerical ranges described in stages in this specification, the upper limit or lower limit of a numerical range in a certain stage may be replaced with the upper limit or lower limit of a numerical range in another stage. In addition, in the numerical ranges described in this specification, the upper limit or lower limit of the numerical range may be replaced with a value shown in the examples. Furthermore, the upper limit and lower limit values ​​described individually can be combined in any combination.

[0014] Hereinafter, an embodiment of the present invention will be described, however, the present invention is not limited to the following embodiment.

[0015] Fig. 1 is a schematic cross-sectional view showing one embodiment of a coated magnesia particle. As shown in Fig. 1, the coated magnesia particle 1 according to one embodiment includes a magnesia particle 2 and a coating layer 3 that coats the surface of the magnesia particle 2. The coating layer 3 may coat at least a part of the surface of the magnesia particle 2, and preferably coats the entire surface of the magnesia particle 2.

[0016] The magnesia particles 2 are particles containing magnesia (magnesium oxide) and may be particles made of magnesia. The average particle size of the magnesia particles 2 may be, for example, 25 μm or more, 50 μm or more, or 70 μm or more, and may be 150 μm or less, 130 μm or less, or 100 μm or less.

[0017] The average particle size in this specification means a value obtained as the average particle size (D50) of particles by mass-based particle size distribution measurement by laser diffraction light scattering method (for example, using "MT3300EXII" manufactured by Microtrackbell Co., Ltd.). For measurement, 0.6 g of particles and 60 ml of water are mixed in an autosampler, and as a pretreatment, a dispersion treatment is performed for 60 seconds with an output of 200 W (for example, using "Ultrasonic Generator UD-200 (with microchip TP-040)" manufactured by Tommy Seiko Co., Ltd.). After the dispersion treatment, 20 ml of a 1% by mass solution of sodium hexametaphosphate is mixed as a dispersant, and the obtained sample is used for measurement. The refractive index of water is 1.33, and the refractive index of magnesia particles and coated magnesia particles is 1.74.

[0018] The average sphericity of the magnesia particles 2 is not particularly limited and may be, for example, less than 0.90. According to the manufacturing method of the embodiment described later, even if the average sphericity of the magnesia particles 2 is less than 0.90, the average sphericity of the obtained coated magnesia particles 1 can be 0.90 or more.

[0019] The average sphericity in this specification means a value measured by the following method. First, the particles are mixed with ethanol to prepare a slurry with a particle concentration of 1% by mass. Next, a Branson "SONIFIER450 (crushing horn 3 / 4" solid type)" is used to perform a dispersion process at output level 8 for 2 minutes. The obtained dispersion slurry is dropped onto a sample stage coated with carbon paste using a dropper. The dropped slurry is left to stand on the sample stage in the air until it dries, after which osmium coating is performed to obtain a measurement sample. Next, the measurement sample is photographed using a scanning electron microscope (for example, a scanning electron microscope "JSM-6301F" manufactured by JEOL Ltd.). The photograph is taken at a magnification of 3000 times, and an image with a resolution of 2048 x 1536 pixels is obtained. The obtained image is imported into a photographing computer, and an image analyzer (for example, an image analyzer "MacView Ver.4" manufactured by Mountec Co., Ltd.) is used to recognize particles using a simple import tool, and the projected area (A) and perimeter (PM) of the particles are measured. The measured projected area (A) and perimeter (PM) are calculated using the following formula: Sphericity=A×4π / (PM) 2 The sphericity of the particles is calculated according to the following: If we assume a perfect circle (radius r, area B) with the same perimeter as the measured perimeter (PM), the sphericity of the measured particle is A / B, where PM=2πr and B=πr. 2 Therefore, B = π × (PM / 2π) 2 The sphericity (A / B) of the measured particle is calculated as follows: A×4π / (PM) 2 It becomes. Then, the sphericity of any 200 particles such that the diameter 2r of the perfect circle obtained from the measured perimeter (PM) is 2 μm or more is calculated as described above, and the arithmetic mean value of these sphericities is taken as the average sphericity.

[0020] The coating layer 3 may contain at least one inorganic oxide other than magnesia (hereinafter, simply referred to as "inorganic oxide"), and may be made of at least one of the inorganic oxides. Examples of inorganic oxides include silica (silicon dioxide) and alumina (aluminum oxide). The inorganic oxide is preferably at least one selected from the group consisting of silica and alumina.

[0021] The thickness of the coating layer 3 is 0.08 to 7 μm. When the thickness of the coating layer 3 is within this range, both high thermal conductivity and moisture resistance can be achieved. From the viewpoint of further improving moisture resistance, the lower limit of the thickness of the coating layer 3 may be preferably 0.1 μm or more, 0.5 μm or more, 0.8 μm or more, or 1 μm or more. From the viewpoint of further improving thermal conductivity, the upper limit of the thickness of the coating layer 3 may be preferably 5 μm or less, 4 μm or less, 3 μm or less, or 2 μm or less.

[0022] The thickness of the coating layer in this specification means a value measured by the following method. First, coated magnesia particles are embedded in epoxy resin, and then the resin is polished to expose the cross section of the coated magnesia, thereby obtaining a measurement sample. Next, the measurement sample is photographed using a scanning electron microscope (for example, a scanning electron microscope "JSM-6301F" manufactured by JEOL Ltd.). The photograph is taken at a magnification of 15,000 times, and an image with a resolution of 2048 x 1536 pixels is obtained. The obtained image is imported into a photographing computer, and using an image analyzer "MacView Ver. 4" manufactured by Mountec Co., Ltd., the cross section of the coated magnesia particle is recognized using a simple import tool, and the thickness of the coating layer (one location) is measured. The thickness of the coating layer of 200 randomly selected coated magnesia particles is then measured as described above, and the arithmetic mean value of these thicknesses is taken as the coating layer thickness (average thickness).

[0023] The average particle diameter of the coated magnesia particles 1 is preferably 30 to 150 μm from the viewpoint of further increasing thermal conductivity and improving dispersibility in resin. The lower limit of the average particle diameter of the coated magnesia particles 1 may be preferably 50 μm or more, 70 μm or more, or 80 μm or more, and may be 140 μm or less, 120 μm, or 100 μm or less, from the viewpoint of further increasing thermal conductivity.

[0024] The average sphericity of the coated magnesia particles 1 is 0.90 or more. When the average sphericity of the coated magnesia particles 1 is within this range, it is possible to achieve both high thermal conductivity and moisture resistance, and also to improve the dispersibility of the coated magnesia particles 1 in resin. From the viewpoint of more suitably obtaining the above-mentioned effects, the average sphericity of the coated magnesia particles 1 may be preferably 0.91 or more, 0.93 or more, or 0.95 or more.

[0025] Next, a description will be given of a method for producing the above-described coated magnesia particles 1. One embodiment of the present invention is a method for producing coated magnesia particles 1, which includes a step of spraying a raw material containing magnesia particles 2 and particles of an inorganic oxide other than magnesia into a high-temperature field heated to a temperature equal to or higher than the melting point of the inorganic oxide particles, thereby coating the surfaces of the magnesia particles 2 and forming a coating layer 3 containing an inorganic oxide (hereinafter also referred to as a "coating / spheroidizing step").

[0026] In the coating and spheroidizing process, first, a raw material is prepared. The magnesia particles 2 in the raw material are the same as the magnesia particles 2 in the above-mentioned coated magnesia particles 1. The larger the average particle diameter of the magnesia in the raw material, the larger the average particle diameter of the obtained coated magnesia particles 1 will be, and the smaller the average particle diameter of the magnesia in the raw material, the smaller the average particle diameter of the coated magnesia particles 1 will be.

[0027] The inorganic oxide particles other than magnesia (hereinafter, simply referred to as "inorganic oxide particles") are particles containing at least one type of inorganic oxide other than magnesia, and may be particles consisting of at least one type of the inorganic oxide. Specific examples of the inorganic oxide are the same as those described above as the inorganic oxide in the coating layer 3. The average particle size of the inorganic oxide particles may be, for example, 0.1 μm or more, and 3.0 μm or less or 0.5 μm or less.

[0028] The raw material may contain only the magnesia particles 2 and inorganic oxide particles, or may further contain other components in addition to the magnesia particles 2 and inorganic oxide particles. Examples of other components include a dispersion medium for dispersing the magnesia particles 2 and inorganic oxide particles. Examples of the dispersion medium include water, and organic dispersion media such as methanol and ethanol can also be used for the purpose of adjusting the calorific value. These dispersion media may be used alone or in combination of two or more.

[0029] In order to obtain coated magnesia particles 1 having the above-mentioned specific thickness of coating layer 3 and average sphericity, the content of magnesia particles 2 in the raw material is 70 to 95 parts by mass per 100 parts by mass of the magnesia particles 2 and inorganic oxide particles in total. The lower limit of the content of magnesia particles 2 may be 80 parts by mass or more or 85 parts by mass or more per 100 parts by mass of the magnesia particles 2 and inorganic oxide particles in total. The upper limit of the content of magnesia particles 2 may be 93 parts by mass or less per 100 parts by mass of the magnesia particles 2 and inorganic oxide particles in total.

[0030] In the coating and spheroidizing step, the raw material is then sprayed into a high-temperature field to melt and solidify the inorganic oxide particles on the surface of the magnesia particles 2. As a result, a coating layer 3 is formed on the surface of the magnesia particles 2, and coated magnesia particles 1 are obtained. By forming the coating layer 3 by melting and solidifying the inorganic oxide particles, coated magnesia particles 1 with high sphericity are obtained. If the raw material is a slurry containing a dispersion medium, the sphericity of the coated magnesia particles 1 tends to be improved when the slurry raw material is sprayed due to the surface tension of the dispersion medium.

[0031] The high-temperature field may be, for example, a high-temperature flame formed in a combustion furnace or the like. The high-temperature flame may be formed by a combustible gas and a combustion supporting gas. As the combustible gas, for example, one or more of propane, butane, propylene, acetylene, hydrogen, etc. may be used. As the combustion supporting gas, for example, an oxygen-containing gas such as oxygen gas may be used. However, the combustible gas and the combustion supporting gas are not limited to these.

[0032] The temperature of the high-temperature field may be equal to or higher than the melting point of the inorganic oxide particles in the raw material, and may be, for example, 1600°C or higher, 1800°C or higher, 2000°C or higher, or 2100°C or higher, and may be 2300°C or lower.

[0033] The raw material can be injected (sprayed) using, for example, a two-fluid nozzle. A dispersion gas may be used when injecting the raw material. That is, the raw material (or a slurry containing the raw material) may be injected while being dispersed in the dispersion gas. This makes it easier to improve the sphericity of the coated magnesia particles 1. As the dispersion gas, a combustion-supporting gas such as air or oxygen, or an inert gas such as nitrogen or argon can be used, and a combustible gas can also be mixed in order to adjust the calorific value of the gas.

[0034] The coated magnesia particles 1 described above can be suitably used as a filler for heat dissipation materials because it can achieve both high thermal conductivity and moisture resistance. That is, another embodiment of the present invention is a filler for heat dissipation materials containing the coated magnesia particles 1 described above.

[0035] The filler for heat dissipation material may contain only the coated magnesia particles 1, or may further contain other particles in addition to the coated magnesia particles 1. Examples of the other particles include alumina particles, silica particles, boron nitride particles, and silicon nitride particles. The content of the coated magnesia particles 1 may be, for example, 10% by volume or more, 30% by volume or more, or 50% by volume or more, and 90% by volume or less, 80% by volume or less, or 70% by volume or less, based on the total amount of the filler for heat dissipation material.

[0036] When the coated magnesia particles 1 are used as a filler for a heat dissipation material, they are used in a state of being mixed with a resin, for example. That is, another embodiment of the present invention is a resin composition containing the coated magnesia particles 1 and a resin. The resin composition may further contain the other particles described above.

[0037] Examples of resins include silicone resin, epoxy resin, acrylic resin, phenolic resin, melamine resin, urea resin, polyester resin, fluororesin, polyimide resin, polyamideimide resin, polyetherimide resin, polycarbonate resin, ABS (acrylonitrile-butadiene rubber-styrene) resin, AAS (acrylonitrile-acrylic rubber-styrene) resin, and AES (acrylonitrile-ethylene-propylene-diene rubber-styrene) resin.

[0038] The resin content may be 5 volume % or more, 10 volume % or more, or 20 volume % or more, and 50 volume % or less, 40 volume % or less, or 30 volume % or less, based on the total amount of the resin composition. The coated magnesia particles 1 content may be 20 volume % or more, 30 volume % or more, or 40 volume % or more, and 80 volume % or less, 70 volume % or less, or 60 volume % or less, based on the total amount of the resin composition. EXAMPLES

[0039] The present invention will be described in more detail below using examples and comparative examples, but the present invention is not limited to the following examples.

[0040] <Example 1> [Preparation of coated magnesia particles] Magnesia particles (Ube Material Industries, Ltd., "RF-70C", average particle size: 80 μm) and alumina particles (Denka Co., Ltd., "ASFP-20", average particle size: 0.8 μm) were mixed, and then water was further mixed to prepare a slurry-like raw material. The mass ratio of magnesia particles:alumina particles:water in the raw material was 9:1:90.

[0041] An apparatus was prepared that was equipped with a combustion furnace with a double-tube LPG-oxygen mixed burner at the top capable of forming inner and outer flames, a collection system line directly connected to the bottom of the combustion furnace, and a blower connected to the collection system line.

[0042] A high-temperature flame of 2100°C was formed in the combustion furnace of the above equipment, and the above slurry and carrier air were sprayed from the center of the burner. The flame was formed by providing several tens of fine holes at the outlet of the burner with a double-tube structure, and spraying a mixed gas of LPG and oxygen from the fine holes. This resulted in the production of coated magnesia particles coated with alumina.

[0043] [Mean sphericity measurement] The average sphericity of the obtained coated magnesia particles was measured by the following method. First, the coated magnesia particles were mixed with ethanol to prepare a slurry with a concentration of the coated magnesia particles of 1% by mass. Then, a Branson "SONIFIER450 (crushing horn 3 / 4" solid type)" was used to perform a dispersion process at output level 8 for 2 minutes. The obtained dispersion slurry was dropped onto a sample stage coated with carbon paste using a dropper. The dropped slurry was left to stand in the air on the sample stage until it dried, and then osmium coating was performed to obtain a measurement sample. Next, the measurement sample was photographed using a scanning electron microscope "JSM-6301F" manufactured by JEOL Ltd. The photographs were taken at a magnification of 3000 times, and images with a resolution of 2048 x 1536 pixels were obtained. The obtained images were imported into a computer for photographing, and using an image analysis device "MacView Ver.4" manufactured by Mountec Co., Ltd., the coated magnesia particles were recognized using the easy import tool, and the projected area (A) and perimeter (PM) of the coated magnesia particles were measured. From the measured projected area (A) and perimeter (PM), the following formula: Sphericity=A×4π / (PM) 2 The sphericity of the coated magnesia particles was calculated according to the above. Then, assuming a perfect circle having the same perimeter as the measured perimeter (PM), the sphericity of 200 arbitrary coated magnesia particles whose diameter is 2 μm or more was calculated as above, and the arithmetic mean value of the sphericities was taken as the average sphericity.

[0044] [Measurement of average particle size] The average particle diameter (D50) of the coated magnesia particles was determined by mass-based particle size distribution measurement by laser diffraction light scattering method using "MT3300EXII" manufactured by Microtrackbell Co., Ltd. In the measurement, 0.6 g of the coated magnesia particles and 60 ml of water were mixed in an autosampler, and as a pretreatment, a dispersion treatment was performed for 60 seconds at an output of 200 W using "Ultrasonic Generator UD-200 (with micro tip TP-040)" manufactured by Tommy Seiko Co., Ltd. After the dispersion treatment, 20 ml of a 1 mass % solution of sodium hexametaphosphate was mixed as a dispersant, and the obtained sample was used for measurement. The refractive index of water was 1.33, and the refractive index of the coated magnesia particles (magnesia particles in Comparative Example 3 described later) was 1.74.

[0045] [Measurement of coating layer thickness] The thickness of the coating layer of the coated magnesia particles was measured by the following method. First, the coated magnesia particles were embedded in an epoxy resin, and the resin was then polished to expose the cross section of the coated magnesia, thereby obtaining a measurement sample. Next, the measurement sample was photographed with a scanning electron microscope "JSM-6301F" manufactured by JEOL Ltd. The photograph was taken at a magnification of 15,000 times, and an image with a resolution of 2048 x 1536 pixels was obtained. The obtained image was imported into a photographing computer, and the cross section of the coated magnesia particle was recognized using the simple import tool with an image analyzer "MacView Ver.4" manufactured by Mountec Co., Ltd., and the thickness of the coating layer (one location) was measured. Then, the thickness of the coating layer of 200 randomly selected coated magnesia particles was measured as described above, and the arithmetic mean value of these thicknesses was taken as the coating layer thickness (average thickness).

[0046] [Making heat dissipation sheets] 10% by volume of silicone resin ("SE1885A" manufactured by Shin-Etsu Chemical Co., Ltd.), 10% by volume of silicone resin ("SE1885B" manufactured by Shin-Etsu Chemical Co., Ltd.), 40% by volume of the coated magnesia particles obtained above, 30% by volume of alumina particles ("DAW-07" manufactured by Denka Co., Ltd.), and 10% by volume of alumina particles ("ASFP-40" manufactured by Denka Co., Ltd.) were mixed. The mixture obtained was used to produce a heat dissipation sheet having a thickness of 3 mm using a sheet coater.

[0047] [Evaluation of thermal conductivity and moisture resistance] The thermal conductivity of the heat dissipation sheet was measured using a resin material thermal resistance measuring instrument "TRM-046RHHT" manufactured by Hitachi Technology Services Co., Ltd. The measurement was carried out under the condition of constant load mode and set load of 2N. Next, the heat dissipation sheet whose thermal conductivity had been measured was left for 168 hours in an unsaturated mode under an environment of 130°C and 85 RH% using a HAST tester manufactured by Espec Corp., and subjected to a moisture resistance test. The thermal conductivity of the heat dissipation sheet after leaving it was measured again in the same manner as above.

[0048] <Examples 2 to 3, Comparative Examples 1 to 2> Coated magnesia particles were produced in the same manner as in Example 1, except that the mixing ratio of magnesia particles and alumina particles in the raw materials was changed as shown in Table 1, and each measurement and evaluation were carried out.

[0049] <Example 4> Coated magnesia particles were produced in the same manner as in Example 1, except that silica particles (manufactured by Denka Co., Ltd., "SFP-30M") were used instead of the alumina particles, and the respective measurements and evaluations were carried out.

[0050] <Comparative Example 3> The same measurements and evaluations as in Example 1 were carried out on magnesia particles not provided with a coating layer ("RF-70C" manufactured by Ube Material Industries, Ltd.).

[0051] Table 1 shows the raw materials and particle characteristics (coated magnesia particles in Examples 1 to 4 and Comparative Examples 1 to 2, and magnesia particles in Comparative Example 3) in Examples 1 to 4 and Comparative Examples 1 to 2, and the thermal conductivity before and after the moisture resistance test in Examples 1 to 4 and Comparative Examples 1 to 3. [Table 1]

[0052] As shown in Table 1, it was found that the coated magnesia particles of Examples 1 to 4 are able to achieve both thermal conductivity and moisture resistance compared to the coated magnesia particles of Comparative Examples 1 and 2 and the magnesia particles of Comparative Example 3 (i.e., at least one of the thermal conductivity before the moisture resistance test and the thermal conductivity after the moisture resistance test does not deteriorate excessively). [Explanation of symbols]

[0053] 1...coated magnesia particle, 2...magnesia particle, 3...coating layer.

Claims

1. A coated magnesia particle comprising a magnesia particle and a coating layer that coats the surface of the magnesia particle, the coating layer contains an inorganic oxide other than magnesia, The coating layer has a thickness of 0.08 to 7 μm, The coated magnesia particles have an average sphericity of 0.90 or more.

2. 2. The coated magnesia particles according to claim 1, wherein the average particle size of the coated magnesia particles is 30 to 150 μm.

3. 3. The coated magnesia particles according to claim 1, wherein the inorganic oxide is at least one selected from the group consisting of silica and alumina.

4. A filler for heat dissipating materials, comprising the coated magnesia particles according to any one of claims 1 to 3.

5. A resin composition comprising the coated magnesia particles according to any one of claims 1 to 3 and a resin.

Citation Information

Patent Citations

  • Powder for selective laser sintering (SLS) / selective laser melting (SLM) as well as preparation method and application thereof

    CN108752014A

  • Highly thermal conductive epoxy resin molding material

    JP1986283648A

  • Production of magnesia powder resistant to hydration

    JP1988045117A

  • Magnesium oxide powder

    JP1989045716A

  • Core-shell type structure, manufacturing method thereof, and heat conductive resin composition

    JP2015199625A